Workshop for Preparation of Minimum Competence Assessment for Private High School Teachers - setyaedhi, hari; Rusijono, Rusijono; Khotimah, Khusnul (Universitas Pendidikan Ganesha, 2023)
The problem faced by private high school teachers is that they are not yet skilled in developing Minimum Competency Assessment (AKM) questions based on numeracy, literacy, and scholastics. This research aims to increase the skills of private high school teachers in preparing Minimum Competency Assessment questions based on numeracy, literacy, and scholastics. This type of research uses a quantitative approach with an experimental design. Data analysis uses descriptive statistics with the help of SPSS. The methods used in this community service are mentoring, lectures, question-and-answer discussions, assignments, practice, and tests. The research subjects were 40 private high school teachers throughout Surakarta. The result found the training went according to the achievement target, namely increasing the teacher's ability to prepare minimum competency assessment questions. This is proven by an increase in the average posttest score of 83, with a pretest average of 61. These results were then t-tested significantly, with results in sig. (2 tailed) = 0.001 < 0.05, which means the pretest and posttest results increased significantly. The implication of this service activity is to increase teachers' abilities in preparing minimum competency assessment questions.